A Multidisciplinary Pathway for the Diagnosis and Prosthodontic Management of a Patient with Medication-Related Osteonecrosis of the Jaw (MRONJ) - Amr S. Bugshan; Yousif A. Al-Dulaijan (Applied Sciences, 2022)
Background: Medication-Related Osteonecrosis of the Jaw (MRONJ) can occur as an adverse reaction to several antiresorptive medications such as bisphosphonate. It presents clinically as a necrotic exposed bone. Several factors including tooth extraction and ill-fitting dentures increase the risk of osteonecrosis development. Case Report: A 72-year-old female who had an ill-fitting partial denture that caused an exposed necrotic bone and traumatic ulcer on the left posterior mandible. Bony sequestrums were removed and submitted for histological examination, which confirmed the diagnosis of MRONJ. Conclusions: This case illustrates the importance of identifying all risk factors associated with MRONJ by dentists to reduce its development in patients receiving antiresorptive medications. Moreover, patients at risk of MRONJ development should be screened carefully on a regular basis and all dental risk factors should be adjusted or removed.